2020
DOI: 10.1111/rda.13776
|View full text |Cite
|
Sign up to set email alerts
|

Effects of slow freezing and vitrification on embryo development in domestic cat

Abstract: Cryopreservation of gametes and embryos combined with other reproductive technologies is an effective way to maintain genetic diversity for mammalian species (Comizzoli & Holt, 2014). Some felids are of great public concern (Cocchia et al., 2015), and domestic cat may be considered as a model species to apply Genome Resource Banking (GRB) to these wild felids (Amstislavsky

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Cryopreservation of lion gametes was not the focus of this study but has been performed successfully for both sperm and oocytes [ 15 , 19 , 41 ]. As with domestic cats, however, the resulting embryos of cryopreserved oocytes have a reduced development potential [ 4 , 42 , 43 , 44 ], and further research is needed to improve freezing techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Cryopreservation of lion gametes was not the focus of this study but has been performed successfully for both sperm and oocytes [ 15 , 19 , 41 ]. As with domestic cats, however, the resulting embryos of cryopreserved oocytes have a reduced development potential [ 4 , 42 , 43 , 44 ], and further research is needed to improve freezing techniques.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies performed in equine and donkey embryos showed that controlled-rate slow freezing seemed to be the most appropriate cryopreservation method [76,77]. Studies on other animal species such as rabbit and cat embryos did not present any difference in survival from the processes of vitrification or controlled-rate slow freezing [78,79]. The literature on other animal species embryo cryopreservation presents contradictory results.…”
Section: Controlled-rated Slow Freezing Versus Vitrification: Advanta...mentioning
confidence: 99%